COVID-19 : A Huge Opportunity for Innovation in Marketing - Pillania, Rajesh K. (Indian Journal of Marketing, 2020)
Peter Drucker famously said that innovations and marketing are the only two basic functions of a business enterprise. Further, innovations are a great way to enhance marketing function. Historically, pandemics and recessions led to more innovations and an overall improvement in life in the long term. The greatest of all pandemics, the Great Plague of 1331–1353, brought several innovations such as more parity in the society as compared to the past, and creation of modern science-based medicine. Pandemics and recessions in the past forced companies to innovate with fewer resources. COVID-19 is a great godsend opportunity to invest in innovations for marketing. It is a time to grow strategically as done by Airbnb, which started in December 2007, and used the recession of 2008 to make it big with its innovative ideas. Contrary to general perception, instead of stopping funding innovations during crisis times, great companies in the past put focused efforts and funds to come up with innovations during crisis times. Some companies are using COVID-19 as a shock therapy to kill the inertia against innovation. The increased risk perception has created opportunities for marketing innovations. The learning from the innovation examples in the 7Ps of marketing shared in the paper is that many companies and government departments have already come up with innovations to face the changed reality. It has implications for practitioners, academicians, and researchers. One interesting idea for future research is to come up with a cause-and-effect model for investments in marketing innovations during crisis times.